Reformy uniwersytetów europejskich. Państwo dobrobytu jako brakujący kontekst badań i polityki publicznej - Kwiek, Marek (Człowiek i Społeczeństwo, 2015)
This paper is focused on the links between reform agendas and their rationales in higher education and in welfare state services across Europe. Lessons learnt from past and ongoing welfare state reforms can be useful in understanding ongoing and future higher education reforms. Research on reforming European welfare states is a missing context in research on reforming European universities. We intend to fill this gap and briefly explore possible links between these two largely isolated policy and research areas. European universities and European welfare states are closely linked today because they are heavily dependent on public funding – and the competition for public funding between the different claimants to it is on the rise. Reforms of both sectors are also closely linked to increasing intergenerational conflicts over public resources in aging societies, and pressures on both sectors are linked to the shrinking tax base, the power of the neoliberal ideology, and changing social attitudes to both welfare and universities. Problems of both sectors and solutions to them are increasingly being defined at a global level through transnational reform discourses.